Existence of solutions for a mixed fractional boundary value problem - Lakoud, Assia Guezane; Khaldi, Rabah; Kilicman, Adem (SpringerOpen, 2017)
In this paper, we prove the existence of solutions for a boundary value problem involving both left Riemann-Liouville and right Caputo-type fractional derivatives. For this, we convert the posed problem to a sum of two integral operators, then we apply Krasnoselskii’s fixed point theorem to conclude the existence of nontrivial solutions.